Stress, Resilience, Burnout and Study Hours in Physical Education Pre-Service Teachers—An Explanatory Model about Gender - Melguizo-Ibáñez, Eduardo; González-Valero, Gabriel; Alonso-Vargas, José Manuel; Caracuel-Cáliz, Rafael Francisco; Ortega-Caballero, Manuel; Puertas-Molero, Pilar (Behavioral Sciences, 2024)
The process of becoming a public teacher in Spain requires a long period of preparation. This long period of preparation has an impact on the psychosocial environment of the candidates. Differences have been observed in the psychosocial area according to gender in pre-service teachers. This research aims to study the relationship between the study hours per day, stress, burnout syndrome and resilience according to gender and to study the differences in the effects according to gender using multigroup equation modeling. A multigroup structural equation analysis has been proposed according to the gender of the participants. Parametric tests were used for the descriptive analysis of the results. The sample consists of 4117 participants, 1363 males and 2754 females. The instruments used to collect the data were a self-made questionnaire, Perceived Stress Questionnaire, Connor-Davidson Resilience Scale and Maslach Burnout Inventory. All the instruments have been validated and adapted to the sample. The data reveal that there are variations in the effects of the variables according to the gender of the participants. In conclusion, it is affirmed that gender is a very important factor in coping with the competitive examination process for state-public-teaching institutions, as well as in avoiding the appearance of disruptive states generated by this preparation process.
Keywords: mental health; physical education teacher; Spanish educational system; gender; Scopus